2018
DOI: 10.1186/s12871-018-0642-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prebiotic galacto-oligosaccharide on postoperative cognitive dysfunction and neuroinflammation through targeting of the gut-brain axis

Abstract: BackgroundSurgery-induced neuroinflammation plays an important role in postoperative cognitive dysfunction (POCD). Gut microbiota is a key regulator of neurological inflammation. Nurturing with prebiotics is an effective microbiota manipulation that can regulate host immunity and cognition. The aim of the present study was to test whether administration of the prebiotic Bimuno® (galactooligosaccharide (B-GOS) mixture) could ameliorate POCD and attenuate surgery-induced neuroinflammation through the microbiota-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 54 publications
(63 reference statements)
1
61
0
1
Order By: Relevance
“…There are multiple reports that investigate the ameliorating effect of oligosaccharides, sugars, and proteoglycans on inflammation [15,[82][83][84][85][86]. However, there are just a few papers [87,88], that focus on their effect on other aspects of complex diseases such as UC and CD. In the present study, we demonstrated that the modulation of the host microflora by a monosaccharide fucose did not affect the severity of the chronic colitis in terms of the intestinal inflammatory response, but partially ameliorated the changes in metabolism and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple reports that investigate the ameliorating effect of oligosaccharides, sugars, and proteoglycans on inflammation [15,[82][83][84][85][86]. However, there are just a few papers [87,88], that focus on their effect on other aspects of complex diseases such as UC and CD. In the present study, we demonstrated that the modulation of the host microflora by a monosaccharide fucose did not affect the severity of the chronic colitis in terms of the intestinal inflammatory response, but partially ameliorated the changes in metabolism and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical work indicates that anesthetics can alter the diversity of the gut microbiome (Serbanescu et al., ), suggesting that a consequent increase in gut permeability may contribute to the raised levels of proinflammatory cytokines. In this context, it may also be of note that prebiotics have been shown to decrease the incidence of POCD in preclinical models (Yang, Wang, Wu, & Jiao, ). Heightened levels of postoperative proinflammatory cytokines can also prevent the synthesis of pineal melatonin (Pontes, Cardoso, Carneiro‐Sampaio, & Markus, ), suggesting that the raised cytokine levels evident in the Light group, may be associated with alterations in circadian regulation, as well as the antioxidant, anti‐inflammatory, and mitochondria‐optimizing effects of melatonin (Polyakova et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Eight-week old rats ( n = 24) were randomly allocated to receive equal concentrations of prebiotic fibres in the drinking water (PREB; 7.5 g/L of galactooligossaccharides and fructooligosaccharides; source: Healy group, Tallaght, Dublin, Ireland) with ad libitum access for 4-weeks to promote the growth of beneficial host microbiota. Concentrations and prebiotics (galactooligossaccharides and fructooligosaccharides) were chosen based on results from previous studies [45] , [46] , [47] . After 2 weeks of PREB treatment, a subset of rats were exposed to CIH (see Section 2.4 ) for the final 2 weeks creating two groups: Sham+PREB ( n = 12) and CIH+PREB ( n = 12).…”
Section: Methodsmentioning
confidence: 99%